A pilot exploratory study for analysis of clinical features and plasma catecholamines in blepharospasm - Lixia Zhu; Hongmei Meng; Wuqiong Zhang; Lijuan Wang; Weixuan Zhao; Jiaai Li; Nilupaer Shafeng; Huaiyu Sun; Ting Jiang; Huiqing Liu; Yu Guo; Shuai Hou (Scientific Reports)
Abstract Blepharospasm (BSP) is a common focal movement disorder linked to the basal ganglia and plasma catecholamines (CAs). This study aimed to analyze clinical characteristics of BSP patients and explore the relationship with plasma CAs. Clinical characteristics, clinician-rated scales, and plasma CAs were recorded, including dopamine (DA), 3-methoxytyramine (3-MT), and the 3-MT/DA ratio. Plasma CA levels were measured using liquid chromatography-tandem mass spectrometry. Clinical features, plasma CAs, and metabolite contents were compared between groups. Spearman’s correlation analysis examined the relationship between plasma CA levels, metabolites, and severity of BSP symptoms. We found that dry eye was an independent risk factor for BSP. Coffee consumption history was an independent protective factor against BSP. Compared to healthy controls, patients had increased DA and decreased 3-MT and 3-MT/DA levels. Anxiety severity negatively correlated with 3-MT and 3-MT/DA levels. The decreased 3-MT/DA ratio is more likely to be a potential biomarker of BSP. These findings highlight the importance of abnormal DA metabolism in BSP pathophysiology and suggest that anxiety symptoms may contribute to BSP pathogenesis by affecting CAs, providing new perspectives for future diagnosis, treatment, and prognostic evaluation of BSP.